2022
DOI: 10.3390/nu14132612
|View full text |Cite
|
Sign up to set email alerts
|

Key Challenges to Optimal Therapeutic Coverage and Maternal Utilization of CMAM Program in Rural Southern Pakistan: A Qualitative Exploratory Study

Abstract: Severe Acute Malnutrition (SAM) is a serious public health problem in many low- and middle-income countries (LMICs). Therapeutic programs are often considered the most effective solution to this problem. However, multiple social and structural factors challenge the social inclusion, sustainability, and effectiveness of such programs. In this article, we aim to explore how poor and remote households face structural inequities and social exclusion in accessing nutrition-specific programs in Pakistan. The study s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

5
4

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 43 publications
1
6
0
Order By: Relevance
“…The study results depicted that the primary and secondary education of the mother lessened the malnutrition odds in both female and male children. The findings of the study were also in accordance with previous studies that observed that the significant determinant of malnutrition is the education of the mothers [ 48 , 49 , 50 , 51 ]. The results of this study demonstrated that the odds of both male and female malnutrition were low in the rich and richest wealth status households.…”
Section: Discussionsupporting
confidence: 91%
“…The study results depicted that the primary and secondary education of the mother lessened the malnutrition odds in both female and male children. The findings of the study were also in accordance with previous studies that observed that the significant determinant of malnutrition is the education of the mothers [ 48 , 49 , 50 , 51 ]. The results of this study demonstrated that the odds of both male and female malnutrition were low in the rich and richest wealth status households.…”
Section: Discussionsupporting
confidence: 91%
“…Evidence demonstrates that social and economic constraints among rural women in developing countries obstruct their access to healthcare, often due to geographical isolation, healthcare provider shortages, lack of appropriate funding, and lack of health education ( 14 ). Also, a study from Southern Punjab Pakistan indicates that a lack of cultural and social capital plays a negative role and becomes the cause of their social exclusion ( 15 ).…”
Section: Discussionmentioning
confidence: 99%
“…A study highlighted that in Southern Punjab District (Multan), Pakistan, most of the population was not satisfied with the services provided in basic health units, and the main reasons behind the bad performance were a shortage of medicine and long-distance to healthcare facilities from residential areas [33]. Another study from Pakistan observed that households living near basic healthcare facilities had lower chances of ARI and diarrhea prevalence among their children and indicated that long distance to basic health centers was significantly associated with increased morbidity prevalence [34,35].…”
Section: Discussionmentioning
confidence: 99%